Synthesis, SAR, and Series Evolution of Novel Oxadiazole-Containing 5‑Lipoxygenase Activating Protein Inhibitors: Discovery of 2‑[4-(3-{(R)‑1-[4-(2-Amino-pyrimidin-5-yl)-phenyl]-1-cyclopropyl-ethyl}-[1,2,4]oxadiazol-5-yl)-pyrazol-1-yl]‑N,N‑dimethyl-acetamide (BI 665915) - Takahashi, Hidenori; Riether, Doris; Bartolozzi, Alessandra; Bosanac, Todd; Berger, Valentina; Binetti, Ralph; Broadwater, John; Chen, Zhidong; Crux, Rebecca; De Lombaert, Stéphane; Dave, Rajvee; Dines, Jonathon A; et al. (Journal of medicinal chemistry, 2015)
The synthesis, structure–activity relationship (SAR), and evolution of a novel series of oxadiazole-containing 5-lipoxygenase-activating protein (FLAP) inhibitors are described. The use of structure-guided drug design techniques provided compounds that demonstrated excellent FLAP binding potency (IC50 < 10 nM) and potent inhibition of LTB4 synthesis in human whole blood (IC50 < 100 nM). Optimization of binding and functional potencies, as well as physicochemical properties resulted in the identification of compound 69 (BI 665915) that demonstrated an excellent cross-species drug metabolism and pharmacokinetics (DMPK) profile and was predicted to have low human clearance. In addition, 69 was predicted to have a low risk for potential drug–drug interactions due to its cytochrome P450 3A4 profile. In a murine ex vivo whole blood study, 69 demonstrated a linear dose–exposure relationship and a dose-dependent inhibition of LTB4 production.